PENINGKATAN PENGETAHUAN KADER LANSIA DALAM MEWUJUDKAN PENUAAN YANG SUKSES (SUCCESS FULL AGEING) DI KECAMATAN JEBRES SURAKARTA - Asita Rohmah Mutnawasitoh; Dita Mirawati (P3M Universitas Aisyiyah Surakarta, 2023)
The aging process in the elderly has an effect on the decline of various functions of body systems. The increase in the number of the elderly population is something that needs to be watched out for this can result in an increase in the incidence of non-contagious chronic conditions, an increase in morbidity and disability. The aging process that occurs in the elderly is also related to various problems in the elderly. The development of technology and creativity in the field of physiotherapy leads to develop community service programs in the field of geriatric physiotherapy. Community service with the theme of knowing and preparing succesfull ageing aims to develop, maintain and restore body movement and function in the elderly. The method used in this service is to increase the knowledge of elderly cadres about the preparations that need to be known in realizing succesfull ageing when entering old the knowledge gained by elderly cadres in this activity is expected to be applied and change the behavior of elderly people in order to realize full ageing success. The method used in this service is to approach. From the results of the evaluation and monitoring of activities that have been carried out, it shows positive results, namely increasing knowledge about preparations to realize succesfull ageing so that the incidence of problems in the elderly can be minimized